Bioethics, ethics and legal odontoestomatology - Ciocca Gómez, Luis (Acta Bioethica, 2006)
This study expects to describe the relationship between ethics, bioethics and law, pointing out the dentistsurgeon’s interest upon this area. The principal matters implying today’s bioethics are indicated, such as the complexity of its relationship with law. Emphasis is put upon the poor importance given to bioethics by national and international legislation which could lead to severe bioethical conflicts.